Association of Reproductive History With Motor Function and Disability in Aging Women. Issue 3 (25th November 2019) - Canonico, Marianne; Artaud, Fanny; Tzourio, Christophe; Elbaz, Alexis
Abstract : BACKGROUND/OBJECTIVES: The associations of reproductive history and motor function are controversial. DESIGN: Prospective cohort study with 10 years of follow‐up. SETTING: Three French cities between 1999 and 2011. PARTICIPANTS: A total of 3043 community‐dwelling women from the Three‐City Dijon study population. MEASUREMENTS: We examined the cross‐sectional and longitudinal association of age at menopause, artificial menopause, and parity with walking speed (WS) using linear regression and linear mixed models, respectively. Cox proportional models were used to examine the association of characteristics of reproductive life with disability. RESULTS: Mean baseline WS was 143.8 cm/s. Artificial menopause was associated with slower WS at baseline (β = −3.29; 95% confidence interval [CI] = −5.83 to −0.74; P = .01). Reproductive life characteristics had no effect on change in WS. Increasing age at menopause was associated with reduced disability risk (hazard ratio [HR] for 5‐year increase = 0.92; 95% CI = 0.87‐0.99; P = .02), while parity increased disability risk (HR for ≥3 vs 0 children = 1.53; 95% CI = 1.22‐1.93; P < .01). CONCLUSION: These findings show that early age at menopause and higher parity have a deleterious effect on motor function that persists in older people. J Am Geriatr Soc 68:585–594, 2020